Nonlinear optical properties in open‐shell molecular systems. (March 2016) - Nakano, Masayoshi; Champagne, Benoît
Abstract : Abstract : For more than 30 years, nonlinear optical (NLO) properties of molecular systems have been actively studied both theoretically and experimentally due to their potential applications in photonics and optoelectronics. Most of the NLO molecular systems are closed‐shell species, while recently open‐shell molecular species have been theoretically proposed as a new class of NLO systems, which exhibit larger NLO properties than the traditional closed‐shell NLO systems. In particular, the third‐order NLO property, the second hyperpolarizability γ, was found to be strongly correlated to the diradical character y, which is a quantum‐chemically defined index of effective bond weakness or of electron correlation: the γ values are enhanced in the intermediate y region as compared to the closed‐shell ( y = 0) and pure open‐shell ( y = 1) domains. This principle has been exemplified by accurate quantum‐chemical calculations for polycyclic hydrocarbons including graphene nanoflakes, multinuclear transition‐metal complexes, main group compounds, and so on. Subsequently, some of these predictions have been substantiated by experiments, including two‐photon absorption. The fundamental mechanism of the y–γ correlation has been explained by using a simple two‐site model and the valence configuration interaction method. On the basis of this y–γ principle, several molecular design guidelines for controlling γ have been proposed. They consist in tuning the diradical characters through chemical modifications of realistic open‐shell singlet molecules. These results open a new path toward understanding the structure—NLO property relationships and toward realizing a new class of highly efficient NLO materials. WIREs Comput Mol Sci 2016, 6:198–210. doi: 10.1002/wcms.1242